معاني القرآن 2026-02-15T15:39:51+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - الفراء، يحيى بن زياد (دار الكتب والوثائق القومية،, 2013)

(untitled)
يتناول معاني القرآن الكريم